Lacrimal Outflow Mechanisms and the Role of Scintigraphy: Current Trends - Detorakis, Efstathios; Zissimopoulos, Athanassios; Ioannakis, Konstantinos; Kozobolis, Vassilios (World Journal of Nuclear Medicine, 2014)
Lacrimal outflow can be compromised by anatomical obstructions or stenoses (nonfunctional epiphora) or by defective lacrimal "pump" function (functional epiphora). Although classic imaging modalities, such as X-ray dacryocystography, computed tomography, or magnetic resonance imaging can effectively evaluate the former, their success is much less in the evaluation of the latter. This is largely due to the fact that forced diagnostic injection of fluid into the canalicular system can overcome partial obstruction sites. On the other hand, lacrimal scintigraphy mimicks "physiological" lacrimal outflow, being performed under pressure gradients present in everyday life. This is why it is considered more suitable for the study of functional epiphora. Furthermore, quantitative lacrimal scintigraphy (with time-activity curves) enables the accurate measurement of lacrimal clearance from the conjunctival fornices and may be used to study the physiology of the lacrimal "pump." Data obtained from the scintigraphic study of lacrimal outflow may be used to design more effective procedures in the management of functional and nonfunctional epiphora. This is a review article, based on a literature search with emphasis on recent publications and on those supporting interdisciplinary cooperation between ophthalmology and nuclear medicine.
Keywords: Canalicular stenosis; dacryocystorhinostomy; epiphora; lacrimal pump; lacrimal scintigraphy; nasolacrimal duct stenosis